EFFECTS OF OCCUPATIONAL HEALTH AND SAFETY CULTURE ON EMPLOYEES’ PERFORMANCE AT AGILITY INTERNATIONAL Ltd., SEMARANG BRANCH - Dian Irawati; Rustono Rustono; Umar Farouk (Politeknik Negeri Semarang, 2018)
This study aims to determine effects of occupational health and safety culture on employees’ performance. To obtain these objectives, questionnaire was distributed to 51 Warehouse Department employees at Agility International Ltd., Semarang Branch. Non Probability sampling namely Simple Random Sampling was used as sampling technique. This study used Rating Scale. SPSS 22nd version and Microsoft Excel 2013 was used to process and test data. Result of this study shows that top management commitment, regulations and procedures, workplace environment, and employees’ involvement have significant effects on employees’ performance partially and simultaneously. The coefficient of determination (Adjusted R Square) is 0.917.